AN EXPLORATION OF LOCAL BRAND DIGITAL COMMUNICATION STRATEGIES ON INSTAGRAM: A CASE STUDY OF @ERIGOSTORE’S USER ENGAGEMENT - Rahayu, Muthia (MediaKom : Jurnal Ilmiah Komunikasi, 2025)
This study analyzes the content strategy of the @erigostore Instagram account in increasing engagement on social media. In Indonesia's dynamic fashion industry, this research explores how Erigo utilizes Instagram to build relationships with consumers. A qualitative case study method is employed to explore visual communication strategies, audience interaction, and the utilization of Instagram features such as Stories, Reels, and influencer collaborations. The theoretical framework includes communication strategies, public relations, new media, and engagement concepts. Using a post-positivist paradigm, the findings indicate that creative and interactive content-based communication strategies significantly enhance Instagram engagement. Key contributing factors include consistent posting, the use of hashtags, and direct interaction, all of which help build a loyal digital community. Erigo implements its strategy through visual branding, captions, collaborations, and platform features. The discussion links findings with the AISAS model and Customer Engagement theory, analyzing how Erigo captures attention, builds interest, encourages search, triggers action, and facilitates experience sharing. The role of visual content, interaction, and collaboration in creating positive experiences and enhancing engagement is emphasized. The study concludes by providing insights into effective social media communication strategies in the local fashion industry and offers practical recommendations for brands to optimize digital communication.